Development of Inquiry-Based Teaching Materials to Improve the Creativity of Prospective Physics Teachers - Lovy Herayanti; Habibi Habibi; Baiq Azmi Sukroyanti (Postgraduate, University of Mataram, 2023)
This research is part of development research at the development stage. Inquiry-based teaching materials developed to increase the creativity of physics teacher candidates have been validated by experts and declared fit for use. At this stage, the aim is to determine the effectiveness of the developed teaching materials in increasing the creativity of prospective physics teachers. The effectiveness of teaching materials developed by researchers can be known by increasing students' creativity based on the results of the N-Gain test after being given a pretest and posttest. The creativity instrument used is a description test which is divided into verbal and figural creativity tests. The pretest average score for the verbal and figural creativity instruments was 62.71 and the posttest average score for creativity was 93.50 both verbal and visual. This value was then analyzed using the N-Gain test with a calculation result of 82.07%, which means that this value is classified into the high increase category. So it can be concluded that the development of inquiry-based teaching materials to increase the creativity of prospective physics teachers is valid and effective